RANCANG BANGUN APLIKASI POINT OF SALE & PENJUALAN ONLINE BERBASIS ANDROID PADA TOKO EMAS - Muhammad Alvin Nugraha Sujana (Universitas Lampung, 2026)
The primary issue at Toko Emas Rahmat Baru is that operational management relies heavily on manual processes. This condition frequently leads to errors in stock and price recording, the risk of data loss, and limited market reach due to the absence of an online sales channel. This study aims to develop